Pengaruh Pelayanan Dan Penghasilan Wajib Pajak Terhadap Kepatuhan Dalam Membayar Pajak Bumi Dan Bangunan (PBB-P2) Pasca Pandemi Covid-19 Di Kecamatan Ngadiluwih Kabupaten Kediri - Amelya One Zarina; Khasanah Sahara; Imarotus Suaida (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This research is motivated by the importance of paying Land and Building Tax for the development of an area because tax revenue is used as an instrument for increasing welfare and can be used for the development of the country, be it facilities, services or other government efforts. Land and building tax is an important income for each region, therefore each local government has its own way of optimizing local revenue from the land and building tax sector. This research aims to find out how much influence service and income have on compliance. This study uses a quantitative method, with primary and secondary data for the 2021 tax year which will be paid in 2022. Sampling used a simple random sampling technique with a total sample of 92 respondents. The analytical method used is instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing. The research results show that the service variable has no influence on compliance, while the income variable has an influence on compliance.